Pengaruh Kesehatan LPD, Jumlah Nasabah dan Suku Bunga Terhadap Proﬁtabilitas Melalui Pertumbuhan Aset - A.A Pt. Agung Mirah Purnama Sari; Ni Made Suindari (Magister Akuntansi Fakultas Ekonomi dan Bisnis Unram, 2020)
The purpose of this study was to analyze the health of Lembaga Perkreditan Desa (LPD) in Badung Regency in 2017-2019. LPD health is measured by CAR, KAP, BOPO, and LDR. Furthermore, CAR, KAP, BOPO, LDR, number of customers and interest rates will be tested for their effect on ROA with asset growth as an intervening variable. Testing was conducted on 103 of 122 LPDs in Badung Regency with CAEL Analysis to analyze the health conditions of the LPDs and Ordinary Least Square to test its effects. The LPD health categories consist of healthy, heallthy enough, less healthy and unhealthy. The results showed that LPDs in the healthy category in Badung Regency had increased from 2017 to 2019 by 1%. In 2017, there were 59% of LPDs in the healthy category and 2019 increased by 60%. Unhealthy LPDs have decreased by 4% since 2017. Other results show CAR, LDR, number of customers and interest rates have a positive effect on ROA. KAP and BOPO have a negative effect on ROA. Meanwhile, asset growth has no effect on ROA. In addition, CAR, BOPO, LDR and interest rates negatively affect asset growth. Meanwhile, KAP and the number of customers have no effect on asset growth. The results of this study also show that asset growth is able to mediate the relationship between the effect of LPD health analysis as proxied by CAR, KAP, BOPO, and LDR, the number of customers and interest rates on ROA. The research implication is focused on the analysis of LPD health, profitability and asset growth so that potential customers can be subject to losses before investing their funds in the LPD. In addition, LPDs are expected to increase their profits and assets by taking into account the CAR, LDR, number of customers and interest rates.